2005
DOI: 10.1089/scd.2005.14.712
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Characterization of Multipotential Mesenchymal Stem Cells Derived from Adult Human Trabecular Bone

Abstract: Much of the knowledge regarding the regulatory pathways for adult stem cell self-renewal and differentiation has been obtained from the results of in vitro cultures. However, it is unclear if adult stem cells are controlled in the same way under physiological conditions. We examined this issue with respect to the migration of stem cells to tissue injury and how switch from a migratory state to one of proliferation wherein they participate in development. Building on our previous identification of multipotent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…For in vitro osteoblastic differentiation, confluent cultures of hFOB cells were maintained in complete medium with the addition of differentiation cocktail as follows: 100 g/l ascorbic acid, 10 Ϫ8 M menadione, 5 mM ␤-glycerol phosphate, and 10 Ϫ7 M 1-25(OH) 2 -vitamin D 3 (all from Sigma) (1). Primary cultures of human osteoblasts were derived from bone chips obtained from healthy individuals undergoing routine orthopedic procedures (37)(38)(39)(40)(41)(42). Isolation of osteoblasts from these de-identified specimens was deemed exempt by the University of Connecticut Health Center Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…For in vitro osteoblastic differentiation, confluent cultures of hFOB cells were maintained in complete medium with the addition of differentiation cocktail as follows: 100 g/l ascorbic acid, 10 Ϫ8 M menadione, 5 mM ␤-glycerol phosphate, and 10 Ϫ7 M 1-25(OH) 2 -vitamin D 3 (all from Sigma) (1). Primary cultures of human osteoblasts were derived from bone chips obtained from healthy individuals undergoing routine orthopedic procedures (37)(38)(39)(40)(41)(42). Isolation of osteoblasts from these de-identified specimens was deemed exempt by the University of Connecticut Health Center Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…For instance studies have identified bone marrow-derived PDGFR-β + /Sca-1 + /CD11b + pericyte progenitors [102], bone marrow-derived CD45 + /CD11b + progenitors [103], and Sca-1 + /Tie2 + /CD13 + pericyte progenitors that have been associated with tumour development [104]. To our knowledge, there is no information on the osteochondrogenic capacity of these cells and as such their potential roles during HO remains unknown.…”
Section: Pericyte Progenitor Cellsmentioning
confidence: 99%
“…These isolated cells had previously been shown to have the potential to become either osteoblasts, adipocytes or chondrocytes and, therefore, have been named ''multipotential mesenchymal stem cells from adult bone''. 15,16 The cells that are grown from human bone also have been shown to be identical in phenotype when differentiated in culture to mesenchymal stem cells obtained from bone marrow aspirates. 17,18 We consider these cells to be multipotential mesenchymal progenitor cells from adult bone but we will call them HOBs representing their differentiated phenotype in the culture conditions employed in this study.…”
mentioning
confidence: 99%